STRUKTUR LIPATAN ANJAKAN DAERAH WALAT, SUKABUMI, JAWA BARAT - -, Iyan Haryanto; -, Edy Sunardi; -, Adjat Sudradjat; -, Suparka (Fakultas Teknik Geologi Universitas Padjadjaran, 2011)
Walat hills in the area of Sukabumi, has a pattern of east-west trending ridge. Hills line orientation is controlled by the structure of fold with is followed by formation of reverse fault. Both of geological structures is formed on the same tectonic period, on Plio-Plistocene. Position of the axis of the fold and reverse fault parallel relative to each other, based on the tectonic formation occurs in the same period, it can be classified as a pattern of thrust folds structure. Of some reverse faults that developed in Walat Area, the reverse fault whose position to northward is major reverse fault, so that by referring to the model structure of Boyer and Elliote (1982), it can be classified as a leading thrust system. This structural pattern is controling topographical differences of the hills with plain morphology in northern.